Multimeric structure of a subfamily III haloalkane dehalogenase-like enzyme solved by combination of cryo-EM and x-ray crystallography - Chmelova, Klaudia; Gao, Tadeja; Polak, Martin; Schenkmayerova, Andrea; Croll, Tristan I; Shaikh, Tanvir R; Skarupova, Jana; Chaloupkova, Radka; Diederichs, Kay; Read, Randy J; Damborsky, Jiri; Novacek, Jiri; et al. (Protein science, 2023)
Haloalkane dehalogenase (HLD) enzymes employ an SN 2 nucleophilic substitution mechanism to erase halogen substituents in diverse organohalogen compounds. Subfamily I and II HLDs are well-characterized enzymes, but the mode and purpose of multimerization of subfamily III HLDs are unknown. Here we probe the structural organization of DhmeA, a subfamily III HLD-like enzyme from the archaeon Haloferax mediterranei, by combining cryo-electron microscopy (cryo-EM) and x-ray crystallography. We show that full-length wild-type DhmeA forms diverse quaternary structures, ranging from small oligomers to large supramolecular ring-like assemblies of various sizes and symmetries. We optimized sample preparation steps, enabling three-dimensional reconstructions of an oligomeric species by single-particle cryo-EM. Moreover, we engineered a crystallizable mutant (DhmeAΔGG ) that provided diffraction-quality crystals. The 3.3 Å crystal structure reveals that DhmeAΔGG forms a ring-like 20-mer structure with outer and inner diameter of ~200 and ~80 Å, respectively. An enzyme homodimer represents a basic repeating building unit of the crystallographic ring. Three assembly interfaces (dimerization, tetramerization, and multimerization) were identified to form the supramolecular ring that displays a negatively charged exterior, while its interior part harboring catalytic sites is positively charged. Localization and exposure of catalytic machineries suggest a possible processing of large negatively charged macromolecular substrates.
Keywords: multimerization; Crystallography, X-Ray; substrátová specifita; krystalografie rentgenová; cryo-EM; Hydrolases; DhmeA; catalysis; x-ray crystallography; elektronová kryomikroskopie; Substrate Specificity; hydrolasy; Haloferax mediterranei; haloalkane dehalogenase; Cryoelectron Microscopy